Reiteration of Jane Eyre's Search for the Feminine Subject in Atkinson's Crime Novels - Esra Melikoğlu (Ideas: Journal of English Literary Studies)
Kate Atkinson in her first and fourth crime novels, Case Histories and Started Early, Took My Dog, rewrites Charlotte Brontë’s Jane Eyre and other Female Gothic narratives to ponder feminism’s failure to ‘arrive.’ Second-wave feminism asks women to retrieve the half-obliterated feminine subject and construct from the fragments an emancipated identity for themselves. In Atkinson’s first crime novel, the amateur detective and actress Julia Land must retrieve a vanished sister and, in the fourth, in her onscreen role as a forensic pathologist the identity of a mutilated sex worker. Yet Julia repeats Jane Eyre’s simultaneous search for a lost woman and complicity with patriarchy’s occlusion of her. Atkinson, it will be argued, signals that the contemporary literary female investigator and ultimately today’s women relive the gothic heroine’s dilemma: Susceptible to the myth of romantic love, they abort their feminist mission and collude with patriarchy’s obliteration of the feminine subject.